2007
DOI: 10.1371/journal.pone.0000842
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Guanine Nucleotide Exchange Factor for Arf3, the Yeast Orthologue of Mammalian Arf6

Abstract: Small G proteins of the Arf and Rab families are fundamental to the organisation and activity of intracellular membranes. One of the most well characterised of these G proteins is mammalian Arf6, a protein that participates in many cellular processes including endocytosis, actin remodelling and cell adhesion. Exchange of GDP for GTP on Arf6 is performed by a variety of guanine nucleotide exchange factors (GEFs), principally of the cytohesin (PSCD) and EFA6 (PSD) families. In this paper we describe the characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…ARF GEFs and ARFs are not highly colocalized (Gillingham and Munro, 2007a;Chun et al, 2008). We found that the majority of Syt1p was colocalized with the late-Golgi and that some Syt1p colocalized with the early Golgi.…”
Section: Dual Localizations Suggests Multiple Roles For Syt1pmentioning
confidence: 64%
See 4 more Smart Citations
“…ARF GEFs and ARFs are not highly colocalized (Gillingham and Munro, 2007a;Chun et al, 2008). We found that the majority of Syt1p was colocalized with the late-Golgi and that some Syt1p colocalized with the early Golgi.…”
Section: Dual Localizations Suggests Multiple Roles For Syt1pmentioning
confidence: 64%
“…Sec7p, Gea1p, Gea2p and Syt1p have been shown to be Arf1/2 GEFs and Yel1p acts as an Arf3p-GEF (Jones et al, 1999;Gillingham and Munro, 2007a;Gillingham and Munro, 2007b). Previous studies have also shown that Sec7p and Yel1p are not …”
Section: Syt1p Regulates Golgi Localization and Activation Of Arl1pmentioning
confidence: 99%
See 3 more Smart Citations